MrMYB6 From Chinese Bayberry (Myrica rubra) Negatively Regulates Anthocyanin and Proanthocyanidin Accumulation - Shi, Liyu; Chen, Xin; Wang, Kang; Yang, Minjie; Chen, Wei; Yang, Zhenfeng; Cao, Shifeng (Frontiers in Plant Science, 2021)
Anthocyanins and proanthocyanidins (PAs) are important flavonoids in Chinese bayberry (Morella rubra), which functions in fruit color and exhibits multiple health promoting and disease-preventing effects. To investigate the regulation of their biosynthesis in Chinese bayberries, we isolated and identified a subgroup 4 MYB transcription factor (TF), MrMYB6, and found MrMYB6 shared similar repressor domains with other MYB co-repressors of anthocyanin and PA biosynthesis after sequence analysis. Gene expression results revealed the transcripts of MrMYB6 were negatively correlated with the anthocyanin and insoluble PA contents and also with the gene expressions involved in anthocyanin biosynthesis and PA specific genes such as MrLAR and MrANR during the late ripening stages of bayberries. In addition, overexpression of MrMYB6 in tobacco inhibited the transcript levels of NtCHI, NtLAR, and NtANR2, resulting into a decline in the levels of anthocyanins and PAs in tobacco flowers. We further found that MrMYB6 interacted with MrbHLH1 and MrWD40-1 to form functional complexes that acted to directly repress the promoter activities of the PA-specific gene MrLAR and MrANR and the anthocyanin-specific gene MrANS and MrUFGT. Taken together, our results suggested that MrMYB6 might negatively regulate anthocyanin and PA accumulation in Chinese bayberry.